Pelayanan Publik pada Sektor Komunikasi - Mohamad Subur Drajat (MediaTor (Jurnal Komunikasi), 2008)
For the most part of society, the quality of public service is far from hope. There were so many problems concerning public service today. One among them was the lack of government capabilities to deal with a very large area and numerous characters. For communication studies, a good public service was influenced by an excellent communication system. There are factors to be deal with: the optimum performance of Public Relations, equal distribution of communication/information, easy access for public, easy access for information, stabilized political situation, and the same pattern of thinking between government and communication manager.